How can Saudi Arabia reform its public hospital payment models? A Nar- rative review (2020)
Background: The cost of Saudi healthcare continues to rise at an alarming rate, putting the sustainability of the public healthcare system into question. Data have shown that hospital and healthcare providers’ services represent the bulk of this rising cost, which makes the calls to reform the Saudi healthcare system more focused on payment models than at any time before. Objective: The aim of this paper is to review various identified payment models that can be used to contain costs and improve the quality of the care provided. Method: A literature review of articles addressing the issues of cost containment and improving the quality of healthcare by reforming the current Saudi healthcare payment policy were identified through the Ovid®, Medline, and Google® Scholar search engines. Results and Conclusions: Many research articles and literature reviews have identified and discussed different models of healthcare payments. Some articles have focused on one payment model, while others have discussed different payment models that have been identified. There is an urgent need to reform the current system of healthcare payments to improve the quality of healthcare and maintain funding for universal healthcare coverage in the future. Future healthcare payment reforms should consider restructuring the current healthcare system, which is largely fragmented by providing incentives to different governmental healthcare sectors, in order to transform it into a more organized and coordinated system. Thus far, there is not a single payment model that can, by itself, reduce healthcare costs and improve healthcare quality. Future healthcare reforms should use a mixture of different payment models to pay hospitals and physicians.